Microfluidics approach to investigate the role of dynamic similitude in osteocyte mechanobiology. Issue 2 (22nd November 2017) - Middleton, Kevin; Kondiboyina, Avinash; Borrett, Michael; Cui, Yi; Mei, Xueting; You, Lidan
ABSTRACT: Fluid flow is an important regulator of cell function and metabolism in many tissues. Fluid shear stresses have been used to level the mechanical stimuli applied in vitro with what occurs in vivo. However, these experiments often lack dynamic similarity, which is necessary to ensure the validity of the model. For interstitial fluid flow, the major requirement for dynamic similarity is the Reynolds number ( Re ), the ratio of inertial to viscous forces, is the same between the system and model. To study the necessity of dynamic similarity for cell mechanotransduction studies, we investigated the response of osteocyte‐like MLO‐Y4 cells to different Re flows at the same level of fluid shear stress. Osteocytes were chosen for this study as flows applied in vitro and in vivo have Re that are orders of magnitude different. We hypothesize that osteocytes' response to fluid flow is Re dependent. We observed that cells exposed to lower and higher Re flows developed rounded and triangular morphologies, respectively. Lower Re flows also reduced apoptosis rates compared to higher Re flows. Furthermore, MLO‐Y4 cells exposed to higher Re flows had stronger calcium responses compared to lower Re flows. However, by also controlling for flow rate, the lower Re flows induced a stronger calcium response; while degradation of components of the osteocyte glycocalyx reversed this effect. This work suggests that osteocytes are highly sensitive to differences in Re, independent of just shear stresses, supporting the need for improved in vitro flow platforms that better recapitulate the physiological environment. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:663–671, 2018.